Russian Rule in Turkestan and the Example of British India ca1865 - 1917 - Morrison, Alexander Stephen (My University, 2006)
This article argues that Russia's Empire in Central Asia is best understood in comparison with the other Western Colonial Empires of the nineteenth century, specifically Britain's Indian Empire. It examines nineteenth-century Russian travellers' accounts of British India, and the `Asianist' tradition which argued that Russians had a greater affinity with Asian peoples than other Europeans, and that the nature of their empire was consequently different. In the case of Turkestan it rejects this assumption on the basis of research in Russian and Uzbek archives, and of the differing views expressed in books and journals by Russian military officers and imperial administrators of the day
Keywords: Central Asia (History); South Asia (History)